Influence de la fiction policière américaine chez trois auteurs de fantasie britannique (Green - Pratchett - Scott) - Catherine Magalhaes (Transatlantica)
Some high fantasy novels borrow a certain number of elements from detective fiction and more precisely from the American roman noir. This recent trend, developed since the 1990s in European as well as American high fantasy, led to the coining of the concept of detective fantasy. This article analyzes the influence of this type of detective fiction on three British high fantasy novels. The characteristics are compared in regard to their structures but also to their themes. This examination is organized around the potential initiation undergone by the protagonists, which is an element inherited from the adventure novel.